2016
DOI: 10.3892/ol.2016.5091
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implication of Tiam1 overexpression in the prognosis of patients with serous ovarian carcinoma

Abstract: Abstract. T lymphoma invasion and metastasis 1 (Tiam1), a guanine nucleotide exchange factor, was originally identified as an invasion-and metastasis-inducing gene in T lymphoma cells. High expression levels of the human Tiam1 gene have been found in numerous human malignancies, suggesting a potential role as a modifier of tumor initiation and progression. However, little is known about the status of Tiam1 in ovarian carcinoma. The present study aimed to investigate the clinicopathological significance of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Finally, a total of 17 studies were included in our meta-analysis. 6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Basic characteristics of included studies A total of 17 studies enrolling 2,228 patients with malignant solid tumors were included in this metaanalysis. The included studies were published from 2006 to 2018.…”
Section: Literature Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a total of 17 studies were included in our meta-analysis. 6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Basic characteristics of included studies A total of 17 studies enrolling 2,228 patients with malignant solid tumors were included in this metaanalysis. The included studies were published from 2006 to 2018.…”
Section: Literature Selectionmentioning
confidence: 99%
“…11,14,16,19,21,22 Besides, 15 studies reported the association between Tiam1 expression and lymph node metastasis. 6,[8][9][10][12][13][14][15][17][18][19][20][21][22][23] All the included studies detected the Tiam1 expression in protein level. More details about the main characteristics of the included studies were presented in Tables 1 and 2.…”
Section: Literature Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of roles in the regulation of cellular functions are exhibited by Tiam1, and these roles depend on the substratum, the specific cell type, and other factors. 15 Li et al and Ding et al confirmed that the overexpression of Tiam1 predicts poor prognosis in ovarian carcinoma and hepatocellular carcinomas, 16 , 17 and Yang et al indicated that upregulation of Tiam1 correlates with poor prognosis in head and neck squamous cell carcinoma. 18 In line with these results, in this study, we assessed the expression level of Tiam1 in PDAC and found for the first time that Tiam1 was upregulated significantly in PDAC compared with that in non-cancerous tissues.…”
Section: Discussionmentioning
confidence: 96%
“…Extensive evidences have illustrated that TIAM1, as a guanine nucleotide exchange factor, is involved in the invasion and metastasis of various human tumors, such as gastric cancer [ 15 ], prostate cancer [ 16 ] and breast cancer [ 17 ]. A previous report uncovered that TIAM1 expression is closely related with the grade and prognosis in OC and might be helpful for the management of clinic [ 18 ]. TIAM1 has also been indicated to facilitate the growth and invasion of OC cells through negatively being regulated by miR-22, miR-183 and miR-31 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%